A case of anterior abdominal wall tuberculosis - Patel, Arpan K.; Bezawada, Ramakrishna; Yootla , Mutheeswaraiah (International Journal Of Community Medicine And Public Health, 2023)
A rare case of a middle-aged woman who presented to our emergency department with a huge swelling over lower part of abdomen for 3 years that was associated with continuous purulent foul-smelling discharge from multiple sites over swelling for past 2 years and all her past history was irrelevant except for her significant loss of weight for 6 months and unable to ambulate due to huge swelling for 6 months. She is known diabetes mellitus type 2 for 6 years on oral hypoglycemic drugs. On examination she had stable vital signs, mild pallor, a large globular swelling of about grossly 30×30×20 cm extending from 2 cm below umbilicus superiorly till pubic symphysis inferiorly, bilaterally extending till anterior superior iliac spine, flanks not full, multiple dilated veins over skin. Multiple foul smelling pus discharging sinuses, prominence on leg raise test and absent cough impulse, rest of the abdomen is soft and non-tender with no organomegaly and present bowel sounds. Bilateral inguinal group of lymph nodes were palpable and matted. Swelling was exclusive extra peritoneal on computed tomography (CT) scan. Excision of swelling was done up to anterior rectus raw area open wound with bilateral inguinal lymph node excision was under general anesthesia was done. Histopathology showed granuloma with caseating necrosis from lymph nodes. Anti-tuberculosis therapy intensive phase was started post operative wound was healthy, and after 6 weeks of initiation of anti-tubercular treatment wound was closed with secondary suturing.